New species of Hammerschmidtiella Chitwood, 1932, and Blattophila Cobb, 1920, and new geographical records for Severianoia annamensis Van Luc & Spiridonov, 1993 (Nematoda: Oxyurida: Thelastomatoidea) from Cockroaches (Insecta: Blattaria) in Ohio and Florida, U.S.A. - Carreno, Ramon A. (Zootaxa, 2017)
Two new species of thelastomatid nematodes parasitic in the hindgut of cockroaches are described. Hammerschmidtiella keeneyi n. sp. is described from a laboratory colony of Diploptera punctata (Eschscholtz, 1822) from a facility in Ohio, U. S. A. This species is characterized by having females with a short tail and males smaller than those described from other species. The new species also differs from others in the genus by a number of differing measurements that indicate a distinct identity, including esophageal, tail, and egg lengths as well as the relative position of the excretory pore. Blattophila peregrinata n. sp. is described from Periplaneta australasiae (Fabricius, 1775) and Pycnoscelus surinamensis (Linnaeus, 1758) in a greenhouse from Ohio, U.S.A. and from wild P. surinamensis in southern Florida, U.S.A. This species differs from others in the genus by having a posteriorly directed vagina, vulva in the anterior third of the body, no lateral alae in females, and eggs with an operculum. In P. surinamensis from southern Florida, an additional species, Severianoia annamensis Van Luc & Spiridonov, 1993 was found and did not co-parasitize the host with B. peregrinata n. sp. Blattophila peregrinata n. sp. and S. annamensis also occur in the Galápagos Islands, Ecuador, indicating that these have a widespread global range.